Folytonos anyagtovábbítású mikrohullámú kezelőegység fejlesztése - Kovács, Róbertné V. P.; Beszédes , Sándor; Ludányi , Lajos; Hodúr, Cecilia; Szabó, Gábor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
Most branches in the food industry have a considerable wastewater output. The problem is not only the total amount of wastewater production, but also the high content of organic matter. Anaerobic digestion is an effective way of treating wastewater for yielding profitable biogas and alleviating environmental concerns. Pre-treatment of sludge to break down its complex structure can be used for enhancing anaerobic digestibility. Research group of the Department of Process Engineering at the University of Szeged has investigated the applicability and the efficiency of microwave pre-treatment for food industry sludge. The results showed that the microwave treatment of sludge solution resulted in higher biodegradability and enhanced biogas production as well. According to these results a continuous-flow microwave toroidal cavity resonator treating-system was developed.